PEMENUHAN HAK WARIS ANAK DALAM PERNIKAHAN SIRI DI BIREUEN (ANALISIS MAQASID SYARIAH) - Tri Mulya Rahmah; Zaiyad Zubaidi; Irwansyah Jamal (AHKAMUL USRAH: Jurnal S2 Hukum Keluarga dan Peradilan Islam, 2024)
Based on article 43 paragraph (1) of the Marriage Law, children born out of wedlock only have civil relations with their mothers and their mother's family. Therefore, serial marriage will annul the rights of wives and children, including in terms of inheritance. In practice, the distribution of inheritance in Bireuen Aceh Regency shows something different. Children from serial marriages are given inheritance and treated like legitimate children, because the child is religiously legitimate. This study aims to determine the provisions of the law on the fulfillment of the inheritance rights of siri married children in the distribution of inheritance property, the mechanism for fulfilling the inheritance rights of children from serial marriages in Bireuen Regency and the review of sharia maqashid on serial marriage children in Bireuen Regency. Research Specifications use qualitative research methods, namely by using content analysis, by describing and describing the content of the findings that the author gets, then connecting with the problems posed so that they can find objective, logical, consistent, and systematic conclusions in accordance with the desired goals, and data collection is guided by facts found when conducting research in the field with an empirical juridical approach. The results showed that, based on the provisions of the legislation, the status of children born from serial marriages is illegitimate children, because the state does not recognize a marriage bond without recording. The child only has a sexual relationship with his mother and his mother's family. The mechanism for the distribution of inheritance to children from serial marriages in Bireuen Regency is carried out based on the rules of Islamic law as well as local customary law with three categories. First, Children who receive the same inheritance rights as children from a registered marriage really depend on the amount of assets left by their parents. Second, children who get inheritance with different amounts from legitimate children by law depend on the success rate of the gampong apparatus in conducting consultations with legal heirs. Third, children who do not get inheritance rights at all from their parents' estate because the property is managed by legal family members based on state provisions, the non-disclosure of the property and also the unwillingness of legal heirs to give the heir's estate. And The fulfillment of inheritance rights for children from serial marriages in Bireuen Regency meets the principles of maqashid sharia hifz al-nafs and hifz al-nasl in the category of children who acquire fully inherited property and partially. With the provisions of the marriage performed fulfill the pillars and conditions in accordance with Islamic law. So that the child from the serial marriage has the same status as the child from the recorded marriage. Therefore, the child of a serial marriage is entitled to a share of the inheritance from both his mother and father's side.